Improving readiness for recruitment through simulated trial activation: the Adjuvant Steroids in Adults with Pandemic influenza (ASAP) trial - Lim, Wei Shen; Meakin, Garry; Brittain, Claire; Bewick, Thomas; Duley, Lelia (BioMed Central, 2017)
Background: Research in public health emergencies requires trials to be set up in readiness for activation at short notice and in anticipation of limited timelines for patient recruitment. We conducted a simulated activation of a hibernating pandemic influenza clinical trial in order to test trial processes and to determine the value of such simulation in maintaining trial readiness. Methods: The simulation involved the Nottingham Clinical Trials Unit, one participating hospital, one manufacturing unit and the Investigational Medicinal Product (IMP) supplier. During the exercise, from 15 September 2015 to 2 December 2015, clinical staff at the participating site completed the trial training package, a volunteer acting as a patient was recruited to the study, ‘dummy’ IMP was prescribed and follow-up completed. Results: Successful activation of the hibernating trial with patient recruitment within 4 weeks of ‘arousal’ as planned was demonstrated. A need for greater resilience in anticipation of staff absenteeism was identified, particularly in relation to key trial procedures where the potential for delay is high. A specific issue relating to the IMP Stock Control System was highlighted as a potential source of error that could compromise the randomisation sequence. The simulation exercise was well received by site investigators and increased their confidence in being able to meet the likely demands of the trial when activated. The estimated cost of the exercise was £1995; 90% of this being staff costs. Conclusions: Simulated activation is useful as a means to test, and prepare for, the rapid activation of ‘hibernating’ research studies. Whether simulation exercises can also help reduce waste in complex clinical trial research deserves further exploration.